ANALISIS ISU SOSIAL MAHASISWA BERBASIS DATA MEDIA SOSIAL MENGGUNAKAN LATENT DIRICHLET ALLOCATION (LDA): Analysis Of Student Social Issues Based On Social Media Data Using Latent Dirichlet Allocation (LDA) - Jesisca, Jesisca; Yonny, Chodri Dwi (Yayasan Al-Amin Qalbu, 2026)
This study aims to identify the most frequently discussed social issues among university student on social media platforms such as TikTok and Instagram. Data were collected via a questionnaire distributed to 50 students, with 49 valid responses analyzed. The Latent Dirichlet Allocation (LDA) method based on linear algebra was applied to classify text data into several main topics. The result revealed three primary clusters of social issues: (1) gender equality and discrimination within the campus environment, (2) educational costs, mental health, and student welfare, and (3) campus politics and career opportunities. Campus politics emerged as the most dominant topic among others. These findings suggest that student actively utilize social media to express their views and respond to institutional policies that directly affect their academic lives. Furthermore, this research demonstrates the effectiveness of the LDA method in analyzing social data to reveal digital communication patterns among student